A Two-layer Optimization Model for Energy Storage System Configuration Considering Life Cycle Cost. Issue 1 (1st February 2023) - Wang, Xueying; Peng, Dong; Zhao, Lang; Xue, Yawei; Lin, Keyao; Hong, Juhua
Abstract: For solving grid voltage fluctuation as a result of the increase of renewable energy penetration, a two-layer optimization strategy considering the life-cycle cost and benefit is proposed. First, a model of life cycle cost-benefit is established to calculate various costs and benefits of energy storage. Then, the combination of genetic algorithms is determined, which is applied to the inner and outer layers. Finally, the proposed optimal configuration strategy is simulated with a Benchmark low-voltage microgrid. The example is given to verify the effectiveness of the proposed method.